Anxiety and It's Relationship with Adherence to Visit Antenatal Care in Pregnant Women - Ainun, Siti Zaimatul; Sari, Gadis Meinar; Frety, Endyka Erye (Journal of Maternal and Child Health, 2022)
Background: Pregnant women were listed as one of the vulnerable groups at risk of being infected with COVID-19 due to physiological changes during pregnancy that result in a decrease in partial immunity. Anxiety experienced by pregnant women causes low compliance in conducting pregnancy tests. This study aims to determine the relationship between anxiety levels and antenatal care compliance in third trimester pregnant women. Subjects and Method: This study used a correlation analytic design with a cross sectional approach. The population in this study were all third trimester pregnant women in Kebonrejo Hasmlet, Kebonrejo Village, Grati District, Pasuruan Regency in November 2021 as many as 37 people. The sampling technique in this research was total sampling. The research instrument used a questionnaire and MCH handbook. Data analysis using Chi-square test.Results: from 37 subjekts, almost all of them experienced mild anxiety, namely 29 subjekts (78.4%), and most of them did not comply with ANC, namely 25 subjects (67.6%).  The chi-square test show that there is a relationship between anxiety levels and ANC compliance in third trimester pregnant women during the COVID-19 pandemic (p<0.001). Conclusion: Anxiety levels was associated with ANC compliance in third trimester pregnant women during the COVID-19 pandemic.